Phase transformations and thermal conductivity of the In-Ag alloys - Manasijevic, Dragan Miroslav; Balanović, Ljubiša; Markovic, Ivana; Gorgievski, Milan; Stamenkovic, Uros; Minic, Dusko; Premovic, Milena; Strbac, Nada (Metallurgical and Materials Engineering, 2020)
Phase transformations and thermal conductivity of three In-Ag alloys with 5, 15, and 45 wt.% of Ag were experimentally investigated in the present work. Phase transition temperatures were measured using differential scanning calorimetry (DSC). DSC heating scans were compared with the equilibrium and non-equilibrium solidification paths, calculated by using optimized thermodynamic parameters from literature and calculation of phase diagrams (CALPHAD) method. The flash method was employed for the determination of thermal diffusivity and thermal conductivity of the investigated alloys in the temperature range from 25 to 100 °C. It has been found that an increase in silver content does not lead to an increase in the thermal conductivity of the investigated alloys. Thermal conductivities for all three investigated In-Ag alloys slightly decrease with temperature increasing.